PENGARUH FEE AUDIT DAN TENURE AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK JAKARTA TIMUR - Dadang Iwan Riswandi (Politeknik Ubaya, 2023)
This research aims to find out whether audit fees, audit tenure and audit quality have an influence, either partially or simultaneously. The population used in this research is Public Accounting Firms in the East Jakarta area. The data collected is primary data taken based on questionnaires distributed to six Public Accounting Firms in East Jakarta. The data that has been collected will be calculated using SPSS 25 in data processing and analysis using the multiple linear analysis method. This research is quantitative research. The research results show that 1) audit fees partially influence audit quality. 2) audit tenure partially influences audit quality. 3) audit fees and audit tenure simultaneously have an influence on audit quality. Then the research results are based on the coefficient of determination test (R2), the R square value shows that audit fees and audit tenure have an effect on audit quality.